Development of a high force density, actuation drive for an aerospace application - Galea, Michael; Buticchi, Giampaolo (2018)
This paper deals with the design, implementation and experimental validation of a complete, electrical drive system, for linear actuation in an aerospace environment, with the main requirements being high force/power density, reliability, availability and fault tolerance. A directly-driven, linear, high force density, tubular motor supplied from a matrix converter for a rotorcraft application is specifically considered. Design aspects of both motor and converter are presented, while an overview of the implementation aspects for the complete drive system is also given. Precise control structures are proposed and tested. Experimental results are presented and compared to the calculated design values. This work shows how the combination of high performance components can achieve a high performance drive in terms of power density and force density.